Wingless-related integration site (WNT) signaling is activated during the inflammatory response upon cardiac surgery: A translational study - Krüger, Bernard D.; Hofer, Gilles E.; Rudiger, Alain; Spahn, Gabriela H.; Braun, Julia; Bettex, Dominique; Schoedon, Gabriele; Spahn, Donat R. (Frontiers in Cardiovascular Medicine, 2022)
Objective Cardiac surgery and the use of cardiopulmonary bypass initiate a systemic inflammatory response. Wingless-related integration site (WNT) signaling is part of the innate immunity and has been attributed a major role in the regulation of inflammation. In preclinical research, WNT-5a may sustain an inflammatory response and cause endothelial dysfunction. Our aim was to investigate WNT signaling after cardiac surgery and its association with postoperative inflammation (Clinicaltrials.gov, NCT04058496). Methods In this prospective, single-center, observational study, 64 consecutive patients for coronary artery bypass grafting (CABG) ± valve surgery were assigned into three groups: off-pump CABG (n = 28), on-pump CABG (n = 16) and combined valve-CABG surgery (n = 20). Blood samples were acquired before surgery, at intensive care unit (ICU) admission and 4, 8, and 48 h thereafter. Plasma concentrations of WNT-5a and its antagonists Secreted frizzled-related protein 1 (sFRP-1), Secreted frizzled-related protein 5 (sFRP-5), and WNT inhibitory factor 1 (WIF-1) were determined by enzyme-linked immunosorbent assay. In addition, plasma concentrations of six inflammatory cytokines were measured by multiplex immunoassay. Parameters were analyzed for evolution of plasma concentration over time, interactions, intergroup differences, and association with clinical outcome parameters. Results At baseline, WNT-5a, sFRP-1, and WIF-1 were present in a minimal concentration, while sFRP-5 was elevated. A higher baseline value of WNT-5a, sFRP-5, and WIF-1 resulted in higher subsequent values of the respective parameter. At ICU admission, WNT-5a and sFRP-5 reached their maximum and minimum value, respectively. WIF-1 decreased over time and was lowest 8 h after surgery. sFRP-1 changed minimally over time. While WNT-5a returned to the baseline within 48 h, sFRP-5 and WIF-1 did not reach their baseline value at 48 h. Of the investigated WNT system components, only WIF-1 partially reflected the severity of surgery. WNT-5a and WIF-1 had an impact on postoperative fluid balance and noradrenaline requirement. Conclusion WNT-5a, sFRP-5, and WIF-1 are part of the systemic inflammatory response after cardiac surgery. WNT-5a peaks immediately after cardiac surgery and returns to baseline within 48 h, presumably modulated by its antagonist sFRP-5. Based on this translational study, WNT-5a antagonism may be further investigated to assess potentially beneficial effects in patients with a dysregulated inflammation after cardiac surgery.